Numerical Evaluation of the Influence of Aggregates on Concrete Compressive Strength at High Strain Rate - Hao, Y.; Hao, Hong (Multi-Science Publishing Co. Ltd., 2011)
The dynamic strength of concrete materials is usually obtained by conducting laboratory tests such as drop-weight test or split Hopkinson pressure bar (SHPB) test. It is widely accepted that the uniaxial compressive strength of concrete and concrete-like material increases with strain rate. Many empirical relations of concrete material dynamic increase factor (DIF), which are proposed for use in the design and analysis, are given in the literature. However, most of these empirical relations were obtained from testing data of concrete-like materials, i.e. the testing specimens were made of mortar matrix only without coarse aggregates owing to constraints in preparing the concrete specimens for high-speed impact tests. Because concrete is a composite material with mortar matrix, interfacial transition zone (ITZ) and aggregates, and these components have different material properties, using specimens made of mortar material alone in tests may not give accurate concrete dynamic material properties. It is also known that the lateral inertia confinement affects the dynamic strength of concrete specimens obtained in impact tests. A number of studies to investigate and quantify the lateral inertia confinement effect on dynamic strength of concrete materials obtained in impact tests have been published. Previous studies also indicate that including aggregates in concrete specimens affects the dynamic strength. However, no systematic study that devotes to investigating the influence of aggregates in concrete specimen on its dynamic strength has been reported yet. In the present study, a mesoscale concrete material model is used to simulate impact tests and to study the influences of aggregates on concrete material compressive strength increment at high strain rates. The commercial software AUTODYN is used to perform the numerical simulations. A method to remove the influence from lateral inertia confinement is proposed and verified. The influence of ITZ on compressive behavior of concrete specimen isdiscussed. Numerical simulations of concrete specimens with different volumetric percentages, e.g. 20% 30% and 40%, of aggregates under impact loads of different loading rates are carried out. The influence of the aggregates on DIF of concrete material is examined and quantified.